Mechanism of the effects of microwave irradiation on the relative volatility of binary mixtures. Issue 4 (6th October 2016) - Li, Hong; Cui, Junjie; Liu, Jiahui; Li, Xingang; Gao, Xin
Abstract : The use of microwave irradiation to enhance distillation processes has been reported recently. However, there is an ongoing debate in the scientific community on whether the observed enhancement is mainly a consequence of the shift of the "equilibrium" of vapor–liquid mass transfer. In this article, a developed instrument was used to determine the relative volatility of various binary mixtures under microwave irradiation. By comparing the relative volatility in the presence/absence of microwave irradiation, the shift of the "equilibrium" of vapor–liquid mass transfer was observed for certain binary mixtures under microwave irradiation. The effects of microwave irradiation on the relative volatility of binary mixtures (in addition to the mechanisms involved therein) were analyzed using the non‐equilibrium thermodynamic principle. The results demonstrate that differences in the dielectric properties, microwave field intensity, intermolecular forces, and boiling point play dominant roles in determining the effects of microwaves on the relative volatility. © 2016 American Institute of Chemical Engineers AIChE J, 63: 1328–1337, 2017